Replication of Grier, Henry, Olekalns and Shields (2004): the Asymmetric Effects of Uncertainty on Inflation and Output Growth - Savva, Christos S. (My University, 2016)
In their influential work Grier et al.(The asymmetric effects of uncertainty on inflation and output growth. Journal of Applied Econometrics 2004; 19: 551–565) examine the effects of growth and inflation uncertainties on their average rates. The current study replicates their main results and performs a similar analysis on a more recent dataset. Their findings are confirmed to a large extent. Copyright © 2015 John Wiley & Sons, Ltd.
Keywords: Econometrics; Asymmetric effects